All in [large type] - Gray, Shelley Shepard (Gray, Shelley Shepard. Bridgeport Social Club series, 2020)
"Meredith Hunt owns and runs a successful Pilates studio, volunteers at the high school every week, and recently bought a house. She can take care of herself -- until she's mugged. When Ace Vance comes to her rescue, she doesn't know how to accept his help -- or stop staring into his chocolate-brown eyes. Ace Vance moved to Bridgeport to offer his fifteen-year-old son, Finn, a better life. And Ace scored a job at a top-notch garage, where he gets to fix up classic cars. Thrown together by a careless criminal, Meredith and Ace can't deny their attraction. But can they open their hearts -- and their lives -- to make room for love?"--Provided by publisher.